Analysis Work-Life Balance and its Impact on Burnout and Employee Performance - Putri, Aisyah Aulia; Jusriadi, Edi; Haanurat, A. Ifayani (Borong Newinera Publisher, 2026)
This study aims to understand in depth the experiences of employees related to Work-Life Balance (WLB), as well as how Work-Life Balance affect the level burnout and their performance at PT Perkebunan Nusantara I Regional 8. This research is descriptive with a qualitative approach using case studies. Ten informants participated in the study. Observation and interviews were used as data collection techniques. In addition, this study also explores employee perceptions of the form of support provided by company management in addressing issues related to work-life balance, work fatigue, and performance achievement. The research results show that most employees of PT Perkebunan I, Regional 8, are able to maintain a balance between work and personal life, although challenges such as high workloads and role conflict persist. Supporting factors include good time management, family support, and flexible policies such as Work from Anywhere Meanwhile, the main obstacles include lack of flexible working hours, excessive workload, and tasks beyond description. Burnout commonly felt, characterized by physical fatigue, emotional stress, and decreased concentration. Work-life balance It has been proven to impact performance, particularly in terms of productivity, work quality, and emotional stability. Therefore, it is important for companies to encourage a work-life balance to maintain optimal employee performance